Globalization, Citizenship and Subjectivity in Modern Family: An Analysis of Community And Changes In The Last Generations. - Sharma, Gudanidhi (Resunga Journal रेसुङ्गा जर्नल, 2024)
Basically, Bourdieu focuses on cultural capital is a major source of social inequality. The conflicts which take place in each social field have specific characteristics arising from those fields and that involve many social relationships which are not economic. Bourdieu developed a theory of the action, around the concept of habitus, which exerted a considerable influence in the social sciences. He introduces theoretical concepts habitus, practice, field, and different forms of capital, such as cultural, economic, social, and symbolic. While gender, class, ethnicity, culture, education, and the historical time period all shape an individual's habitus, what one does in everyday life is dynamic and fluid, like a jazz musician's improvisation on a theme. As we discussed on globalization, citizenship and subjectivity in the family through different generation, whether the globalization directly impact the family life and activities or families themselves have embodied own subjectivity to change interest, habitus and rationality. If we look from the eyes of Bourdieu or as a sociologist, we have to be skeptical of our social beliefs, cultures and should be reflexive.